Manipulating implement weight during warmup to improve shot put performance - Klein, L.; Peach, M.; Whitten, J.; McKibben, K.; Graham, D.; Becker, J. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to evaluate kinematics and kinetics of the shot put when participants warmup using standard, overweight, or underweight implements. Ten collegiate shot putters warmed up using regulation, heavy, or light implements then completed six maximal effort competition throws. Whole body kinematics and ground reaction forces were recorded on each throw. Consistent with the literature, throw distance was significantly further after warming up with the heavy implement (p = .002). However, there were no differences in critical kinematic factors or ground reaction forces between conditions. While using overweight implements during warmup improves shot put performance, the mechanism by which this occurs is not through altering the critical factors or forces produced during the throw.